2021
DOI: 10.3390/healthcare9121739
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perceptions and Satisfaction with the Outpatient Telemedicine Clinics during COVID-19 Era in Saudi Arabia: A Cross-Sectional Study

Abstract: Successful implementation of virtual healthcare depends immensely on patients’ perceptions and satisfaction. This cross-sectional study assessed patients’ perceptions of, and factors associated with, poor and average satisfaction with the outpatient telemedicine clinics in the Kingdom of Saudi Arabia (KSA). This questionnaire-based survey was conducted among 720 patients who attended outpatient telemedicine clinics from different regions of the KSA. Of the sample studied, 54.7% of the participants had high sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…There was an overwhelming response and a high satisfaction rate in regard to the implementation of telemedicine visits via simple telephone calls in response to the COVID-19 pandemic and the lockdown, and the satisfaction rate was comparable to that of the in-person visit service. This observation is similar to those of other studies examining patients’ experiences and satisfaction with telemedicine clinics in osteoporosis management or other chronic diseases during the COVID-19 pandemic [ 13 , 14 ]. Notably, our telehealth consultations were with audio only.…”
Section: Discussionsupporting
confidence: 90%
“…There was an overwhelming response and a high satisfaction rate in regard to the implementation of telemedicine visits via simple telephone calls in response to the COVID-19 pandemic and the lockdown, and the satisfaction rate was comparable to that of the in-person visit service. This observation is similar to those of other studies examining patients’ experiences and satisfaction with telemedicine clinics in osteoporosis management or other chronic diseases during the COVID-19 pandemic [ 13 , 14 ]. Notably, our telehealth consultations were with audio only.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings align with prior research that has shown how the COVID-19 pandemic created barriers to treatment and care services because of the inability of in-person medical visits, staffing disruptions, and fewer blood tests and lab results [ 29 31 ]. Additionally, patients have also reported dissatisfaction with online and virtual telemedicine, including needing longer lead time and planning for medical appointments [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…In addition to supporting the process of training medical personnel to deal with information technology means. For these reasons, the lack of funding is an obstacle to the adoption of the use of information technology in treating Corona patients from a distance [24]. Work regulation: The process of treating Corona patients from a distance using information technology applications must be regulated by special laws that merge with the rules followed in hospitals.…”
Section: C) Organizational Factors −mentioning
confidence: 99%